Making 3D Printed Objects Interactive Using Wireless Accelerometers - Hook, Johnathan; Wright, Peter; Nappey, Thomas; Olivier, Patrick; Hodges, Steve (CHI 2014 Extended Abstracts, 2014)
We present an approach that allows designers and others to quickly and easily make 3D printed objects interactive, without the need for hardware or software expertise and with little modification to an object’s physical design. With our approach, a designer simply attaches or embeds small three-axis wireless accelerometer modules into the moving parts of a 3D printed object. A simple graphical user interface is then used to configure the system to interpret the movements of these accelerometers as if they were common physical controls such as buttons or dials. The designer can then associate events generated by these controls with a range of interactive behavior, including web browser and media player control.